2020
DOI: 10.1038/s41598-020-73072-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land configuration and organic nutrient management on productivity, quality and soil properties under baby corn in Eastern Himalayas

Abstract: Appropriate land configuration and assured nutrient supply are prerequisites for quality organic baby corn (Zea mays L.) production in high rainfall areas of the delicate Eastern Himalayan Region of India. A long term (5-year) study was conducted during 2012–2016 on a sandy loam soil in the mid attitude of Sikkim, Eastern Himalayan Region of India to evaluate the productivity, produce quality, the profitability of baby corn, and soil properties under different land configurations comprising flatbed, ridge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…Waxy corn, a variety of maize expressing the only amylopectin, has been extensively planted in China and many other countries (Ketthaisong et al, 2014). However, maize (Zea mays L.) is considered sensitive to variations in its environment, especially during the seedling stage (Xie et al, 2017;Wang et al, 2018;Babu et al, 2020). In particular, maize is highly sensitive to waterlogging stress, which in the early growth stage, significantly inhibits its growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Waxy corn, a variety of maize expressing the only amylopectin, has been extensively planted in China and many other countries (Ketthaisong et al, 2014). However, maize (Zea mays L.) is considered sensitive to variations in its environment, especially during the seedling stage (Xie et al, 2017;Wang et al, 2018;Babu et al, 2020). In particular, maize is highly sensitive to waterlogging stress, which in the early growth stage, significantly inhibits its growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…In RWS of IGP, increasing sub‐surface soil compaction and depletion of SOC are major concerns of the system's sustainability (Timsina & Connor, 2001; Yadav et al, 2000). Measurable changes in BD and TOC in the 0–15 cm soil depth are generally noticed under long‐term studies (Babu et al, 2020; Bhattacharyya et al, 2011). However, in this study, the positive effect of organic recycling including GR on reduced soil BD (Table 3) and increased TOC (Table 4) was noticed down to 45 cm soil depth.…”
Section: Discussionmentioning
confidence: 96%
“…Strategies for increasing SOC and protecting it for longer periods are crop residue management, the addition of organic amendments, balanced fertilization, minimum soil disturbance, and allowing for diverse crop rotations (Datta et al, 2018; Lal, 2015). Such strategies are much tested for enhancing crop yields, maximization of farm profit, water productivity, and resource use efficiency under various crops and cropping systems (Babu et al, 2020; Iqbal et al, 2019). However, limited information is available on the long‐term effect of combined use of mineral fertilizers and organics in rice ( Oryza sativa L.)‐wheat ( Triticum aestivum L.) system (RWS) on soil C dynamics in deeper soil layers.…”
Section: Introductionmentioning
confidence: 99%
“…Soil nutrient is one of the main indexes to measure soil fertility, and its content directly affects soil fertility supply and crop growth (Ghosh et al 2022 ). Organic matter, N, P and K content are the main sources of soil nutrients, which are the basis of nutrient absorption and utilization for crop maintenance (Babu et al 2020 ). Accumulating evidence has shown that the films mulching can effectively improve soil aggregate structure, bulk density, porosity and other physical structures (Tang et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%